Reliability of acoustic parameters measurement from different trials of voice sample production - Seng, Thong Wai (Universiti Sains Malaysia, 2015)
The present study aims to investigate the number of voice sample production trials required to obtain reliable measurement of acoustic parameters i.e., fundamental frequency, jitter percent, shimmer percent, and harmonic-to-noise ratio. Based on a convenient sampling, a total of 33 males participants were recruited in the present study. Each participant was required to produce sustained vowel /a/ in comfortable pitch and loudness for at least 5 seconds for 15 trials. These voice samples were objectively analyzed to obtain the acoustic parameters of voice. The Intraclass Correlation Coefficients (ICCs) values of 3 to 15 trials for each acoustic parameters were measured to determine the number of trials of voice sample production that produce reliable measurement of acoustic parameters. The finding of the present study demonstrated three voice sample production trials were required to obtain both acceptable and excellent reliability measurement for fundamental frequency, shimmer percent and harmonic-to-noise ratio. For jitter percent, at least four trials of voice sample production were required to obtain acceptable reliability and at least seven trials of voice sample production to acquire excellent reliability measurement. Based on the present study, it is recommended that a minimum of four trials of voice sample production are required to obtain at least acceptable reliability measurement for all acoustic parameters.